The Influence of Personal Selling and Digital Marketing on The Formation of Brand Equity XYZ Insurance Jakarta Branch - Valentina, Virgin; Purnaningsih, Ninuk; Hartoyo (Jurnal Aplikasi Bisnis dan Manajemen, 2023)
XYZ Insurance is an insurance company that has only been running for three years and is considered to have no brand equity (brand strength) in the eyes of customers. The purpose of this research were identify the perception of personal selling and digital marketing on the formation of brand equity, Analyzing the effect of personal selling and digital marketing on the formation of brand equity and Formulate managerial implications that will be applied by XYZ Insurance to increase brand equity. The data processing and analysis techniques used in this study are descriptive analysis and brand equity analysis with structural equation modelling (SEM) with a variance approach (VB-SEM) with partial least squares (PLS-SEM) technique. The results showed that the results showed that both personal selling and digital marketing had a significant effect on brand awareness, brand association, perceived quality, and brand loyalty. While the indirect effect explains that personal selling through brand awareness, brand association, and loyalty variables has a good mediating role on brand equity. Meanwhile, digital marketing through brand awareness, perceived quality, and loyalty variables has a role as a mediating variable, but it is still doubtful because it has an insignificant effect on brand equity. Therefore, it is expected to improve brand equity are in developing the company's brand awareness, both in terms of personal selling agents and developing the use of digital media. Keywords: XYZ Insurance, SEM-PLS, brand awareness, brand loyalty, brand equity